B cell depletion and inhibition in systemic lupus erythematosus. (2nd January 2023) - Krustev, Eugene; Clarke, Ann E.; Barber, Megan R.W.
ABSTRACT: Introduction: Systemic lupus erythematosus (SLE) is characterized by autoantibody expression and aberrant autoreactive B cells contribute to disease progression; therefore, B cell inhibition has been an attractive target for novel therapies. However, after more than two decades of research and over 40 randomized clinical trials, only one such therapy, belimumab, has been approved for use in SLE. Areas covered: In this review, we discuss the evidence for B cell-targeted therapies in SLE and lupus nephritis. Belimumab has been successful in several large clinical trials and is approved in several countries for use in SLE and lupus nephritis. Despite a lack of supporting phase III evidence, rituximab is used off-label in SLE. Several other B cell-targeted therapies have failed to meet their end points in late-stage clinical trials. Successful phase II trials have recently been reported for obinutuzumab and telitacicept with larger confirmatory trials currently underway. Expert opinion: Refinements in pharmaceutical mechanisms of action, trial design, and patient selection have resulted in recent preliminary successes, offering renewed optimism for B-cell targeted therapeutics in SLE management.